The significance of ternary hybrid cross bio-nanofluid model in expanding/contracting cylinder with inclined magnetic field - Alraddadi, Ibrahim; Ayub, Assad; Hussain, Syed Modassir; Khan, Umair; Hussain Shah, Syed Zahir; Hassan, Ahmed M. (Frontiers in Materials, 2023)
The bio-nanofluids have achieved rapid attention due to their potential and vital role in various fields like biotechnology, energy and medicine such as drug delivery, imaging, scaffolds for tissue engineering, suitable environment for cell growth, coolants in various energy systems, used for wastewater treatment, and delivery of nutrients to plants.Objective: The present study proposes a novel mathematical model for the ternary hybrid cross bionanofluid model to analyse the behaviour of blood past through a stenosed artery under the influence of an inclined magnetic field. The model considers the effect of expanding/contracting cylinder, infinite shear rate viscosity, and bio-nanofluids.The consider model of the problem is bounded in the form of governing equations such as PDEs. These PDEs are transformed into ODEs with help of similarity transformations and then solved numerically with the help of bvp4c method.The results show that the flow rate and velocity decrease as the inclination angle of the magnetic field increases. Additionally, it is found that the presence of nanoparticles in the bio-nanofluid has a significant impact on the velocity and flow rate. Therefore, the flow rate decreases, in general, as the stenosis becomes more severe.The results obtained from this study may provide insights into the behaviour of blood flow in stenosed arteries and may be useful in the design of medical devices and therapies for the treatment of cardiovascular diseases.